2014
DOI: 10.1098/rsbl.2013.1103
|View full text |Cite
|
Sign up to set email alerts
|

To keep on track during flight, fruitflies discount the skyward view

Abstract: When small flying insects go off their intended course, they use the resulting pattern of motion on their eye, or optic flow, to guide corrective steering. A change in heading generates a unique, rotational motion pattern and a change in position generates a translational motion pattern, and each produces corrective responses in the wingbeats. Any image in the flow field can signal rotation, but owing to parallax, only the images of nearby objects can signal translation. Insects that fly near the ground might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This hypothesis is supported by the discovery of a neural correlate in that visual interneuron VT1 fires spike bursts when presented with translational cues (Longden et al, 2017). It would be interesting to perform a set of experiments similar to those of Mazo and Theobald (2014) to see whether this model holds true for moths. It would also be interesting for us to perform plume tracking experiments on ventrally painted moths with decreasing altitudes above the floor of the odor plume to see whether we can observe the effects of a loss of translational motion in M. sexta.…”
Section: Plume Tracking and Optomotor Behaviors Unaffected By Lack Ofmentioning
confidence: 90%
See 1 more Smart Citation
“…This hypothesis is supported by the discovery of a neural correlate in that visual interneuron VT1 fires spike bursts when presented with translational cues (Longden et al, 2017). It would be interesting to perform a set of experiments similar to those of Mazo and Theobald (2014) to see whether this model holds true for moths. It would also be interesting for us to perform plume tracking experiments on ventrally painted moths with decreasing altitudes above the floor of the odor plume to see whether we can observe the effects of a loss of translational motion in M. sexta.…”
Section: Plume Tracking and Optomotor Behaviors Unaffected By Lack Ofmentioning
confidence: 90%
“…In light of our results, another question that arises is the function of the ventral compound eye. Mazo and Theobald (2014) found that tethered D. melanogaster responded strongly to translational optic flow presented to the lower half of the visual field and the entire visual field, but less so when presented to the upper half. Their conclusions confirmed a prediction by Krapp and Hengstenberg (1996) that rotational and translational optic flow detection may be different information streams.…”
Section: Plume Tracking and Optomotor Behaviors Unaffected By Lack Ofmentioning
confidence: 94%
“…Since objects below the horizon are typically closer to a fly, there is potentially strong selective pressure to evaluate translational disturbances below the horizon in detail [10,11]. In fact, the ventral region of the eye is mostly insensitive to certain types of rotation [12], while highly responsive to translation [13]. This functional compartmentalization likely reduces redundancy and enhances accuracy in the perception of self-motion during flight (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wide fields of dots that simulate translational or rotational motion produce changes in ΔWBA that work to correct the apparent deviation from a forward heading (Theobald et al, 2010). These responses are robust and repeatable, although the correlation between motion and tracking is often lower than for bars (Mazo and Theobald, 2014). Further, translational motions produce stronger responses than rotational motions, but provide the independent depth cue of motion parallax, and additionally generate responses that inherently vary with elevation (Mazo and Theobald, 2014).…”
Section: Wide-field Tracking Responses Can Also Vary With the Visiblementioning
confidence: 99%
“…These responses are robust and repeatable, although the correlation between motion and tracking is often lower than for bars (Mazo and Theobald, 2014). Further, translational motions produce stronger responses than rotational motions, but provide the independent depth cue of motion parallax, and additionally generate responses that inherently vary with elevation (Mazo and Theobald, 2014). To avoid these effects, we presented rotational flow fields.…”
Section: Wide-field Tracking Responses Can Also Vary With the Visiblementioning
confidence: 99%